Hypoxia promotes stem cell phenotypes and poor prognosis through epigenetic regulation of DICER - Van Den Beucken, T; Koch, E; Chu, K; Rupaimoole, R; Prickaerts, P; Adriaens, M; Voncken, JW; Harris, AL; Buffa, FM; Haider, S; Starmans, MHW; Yao, CQ; et al. (Springer Nature, 2014)
MicroRNAs are small regulatory RNAs that post transcriptionally control gene expression. Reduced expression of DICER, the enzyme involved in microRNA processing, is frequently observed in cancer and is associated with poor clinical outcome in various malignancies. Yet, the underlying mechanisms are not well understood. Here we identify tumour hypoxia as a regulator of DICER expression in large cohorts of breast cancer patients. We show that DICER expression is suppressed by hypoxia through an epigenetic mechanism that involves inhibition of oxygen-dependent H3K27me3 demethylases KDM6A/B and results in silencing of the DICER promoter. Subsequently, reduced miRNA processing leads to derepression of the miR-200 target ZEB1, stimulates the epithelial to mesenchymal transition and ultimately results in the acquisition of stem cell phenotypes in human mammary epithelial cells. Our study uncovers a previously unknown relationship between oxygen-sensitive epigenetic regulators, miRNA biogenesis and tumour stem cell phenotypes that may underlie poor outcome in breast cancer.